Psychosocial impact of parenting children with intellectual disabilities in Bangladesh - Mohammad Aminul Islam; Md. Azibar Rahman; Sharmin Akhtar (Intelektual Pustaka Media Utama, 2022)
It is well documented that raising a child with an intellectual disability negatively affects the mental health and marital relationships of the parents as they encounter additional social, psychological, financial, and physical burdens. But little is known about the phenomena from the context of Bangladesh. This study aimed to investigate the effect of having a child with an intellectual disability on marital satisfaction and the mental wellbeing of the parents. It assessed the depression and marital satisfaction of randomly selected 60 parents (both father and mother) having a child with an intellectual disability and compared with the same number of parents without a child of intellectual disability. It used an improvised Bangla version of the beck depression inventory (BDI-II) and a relationship assessment scale (RAS) to measure the severity of depression and the level of marital satisfaction among the participants. Most of the parents of children with intellectual disabilities suffer from moderate depression. Meanwhile, most of the parents of children without intellectual disabilities suffer from mild mood disturbance. Parents of children with intellectual disabilities suffer from a higher level of depression and have a higher level of marital satisfaction compared to the parents of children without intellectual disabilities in Bangladesh.